1999
DOI: 10.1038/sj.bmt.1701963
|View full text |Cite
|
Sign up to set email alerts
|

Molecular remission in PCR-positive acute myeloid leukemia patients with inv(16): role of bone marrow transplantation procedures

Abstract: be expected, given the prevalence of the normal population to be less than 1%.We conclude that the prothrombin gene variant probably increases the risk of VOD in BMT patients. Identification of high risk patients may allow early detection of events leading to VOD, and early intervention and treatment of this disease. However, it is interesting that the more common thrombophilic trait, FV Leiden, does not appear to be a predisposing factor for VOD. We recognise that the number of patients in our preliminary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…12,17,18 It is thought that some of these patients may be considered cured. This report on a large series of patients with inv(16) AML examines what, to our knowledge, is the longest clinical, cytogenetic, and molecular follow-up thus far published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,17,18 It is thought that some of these patients may be considered cured. This report on a large series of patients with inv(16) AML examines what, to our knowledge, is the longest clinical, cytogenetic, and molecular follow-up thus far published.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Most patients with inv(16) AML treated in our institute achieved long-term CR. 17,18 However, several groups have reported persistence of the chimeric transcript even after allogeneic bone marrow transplantation (BMT). 12,[19][20][21] These considerations prompted us to investigate whether it is possible to predict relapse among patients who have achieved CR, and under what conditions patients can be considered in a curable state.…”
mentioning
confidence: 99%
“…1,2 In these entities most patients achieve a complete remission (CR); however, 10% to 30% finally have a relapse. 1,[3][4][5][6][7][8][9][10] The corresponding leukemia-specific fusion transcripts, PML-RARA, CBFB-MYH11, and AML1-ETO, can be targeted by polymerase chain reaction (PCR)-based methods at diagnosis and to detect minimal residual disease (MRD). [11][12][13] Thus, the presence of residual PML-RARA ϩ cells strongly predicts relapse and therefore is an important parameter for treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to t(8;21) AML, the inv (16) AML studies reported to date have limitations consisting of small numbers of patients analyzed and lack of standardized RT-PCR assays. However, the collective analysis of these data supports the notion that molecular remission is achievable and is likely to be predictive of CCR in this subgroup of AML patients (Table 3) (12,13,(46)(47)(48)(49)(50)(51)(52)(53).…”
mentioning
confidence: 56%
“…In some cases, in fact, the detection of MRD during CR is not indicative of impending relapse, and chimeric transcripts have been found in patients with long‐term clinical remission and in normal healthy individuals (8–10). Similarly, a BM or blood sample deemed negative for MRD on the basis of an undetectable fusion transcript has not been invariably predictive of long‐term remission (11–13). These data support the notion that distinct molecular subgroups of AML may have a diversified biology, and that in some cases, persistence of chimeric clones following aggressive treatment is compatible with normal hematopoiesis.…”
Section: Monitoring Minimal Residual Disease In Acute Myeloid Leukemiamentioning
confidence: 99%